Smile without a reason why: Functional specialisation and income distribution along global value chains - Federico Riccio; Giovanni Dosi; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
This paper addresses two questions namely, first, the extent to which the very participation in Global Value Chains (GVCs) has penalised labour as a globally insourced production input, and, second, what happened to between-occupation functional inequality. We combine input-output (I-O) tables and labour income along the production stages of global value chains. We focus on foreign labour requirements in manufacturing industries and distinguish across four production stages, namely fabrication, marketing, R&D and managerial functions to map the relative specialisation patterns of different production sub-systems. Our results show that GVCs are hierarchically structured, with advanced countries specialising in upstream functions along global production networks. Fabrication workers are the biggest losers in this process, accounting for most of the drop in labour share in developed and developing countries. Considering that production workers make up more than 50% of the workforce in both advanced and developing countries, the labour share loss of blue-collar workers is a major driver of the increasing global wage inequality.
Keywords: F14; J31; O14; 330; Labour Share; Global Value Chains; Functional Specialisation; Comparative Advantages; Income Inequalities; International division of Labour